Whole-genome sequencing, as a powerful diagnostic tool in hearing loss, reveals novel variants in PTPRQ missed by whole-exome sequencing - Daniel Bengl; Asuman Koparir; Wahyu Eka Prastyo; Christian Remmele; Marcus Dittrich; Sophie Flandin; Waafa Shehata-Dieler; Clemens Grimm; Thomas Haaf; Michaela A. H. Hofrichter (BMC Medical Genomics)
Abstract Background/objectives Hearing loss (HL) is one of the most common congenital disorders, affecting 1-2 in 1,000 newborns. Modern genetic diagnostics using large gene panels and/or whole exome analysis (WES) can identify disease-causing mutations in 25-50 % of patients, with higher solve rates in individuals with earlier onset. Results Here, we used whole-genome sequencing (WGS) to reanalyze 14 index patients/families who remained without genetic diagnosis by WES. We were able to identify the genetic cause of HL in 6 families ( $$\sim$$ ∼ 43 %). Two families were diagnosed with DFNB84A caused by compound heterozygous recessive mutations in PTPRQ. Three of the four underlying variants, including a structural variant, a deep intronic variant, and a splice variant, escaped detection by WES. Minigene assays confirmed the pathogenicity of the intronic and the splice variants. In addition, we used protein 3D structure prediction and rigid ligand docking to study the pathogenicity of variants that escape nonsense-mediated decay. Conclusion In our study, we present four novel variants in PTPRQ, three of which were detected only by WGS. To our knowledge, we report here the first pathogenic deep intronic PTPRQ variant causing HL. Our results suggest that the mutational spectrum of PTPRQ is not well covered by standard WES and that PTPRQ-associated hearing loss may be more frequent than previously thought. WGS provides an additional layer of information in the diagnostics of HL.